Designing online information systems for portfolio-based assessment: design criteria and heuristics - Love, Terence; Cooper, T. (Informing Science Institute, 2004)
This paper reports the main findings of an exploratory investigation into the key factors necessary to designing information systems for online portfolio-based assessment in tertiary, professional, secon-dary and primary education that maximize benefits for all stakeholders. A review of contemporary practice in designing online portfolio assessment systems showed a widespread neglect of several key factors necessary to formulating designs that maximize benefits for all stakeholders. In addition, it was found that design processes were marked by an over-emphasis on technical issues to facilitate imple-mentation rather than addressing the primary educational goals. The result is online portfolio systems that fall significantly short of their potential, and, in many cases, are inferior to conventional portfolio assessment and other more traditional assessment approaches.The paper identifies key design factors necessary for successful conceptual design of online portfolio information systems that maximize benefits for all stakeholders. Initial design heuristics are outlined for designing online portfolio assessment information systems that provide improvements on conven-tional portfolio assessment and other assessment modalities for all stakeholders.